Prevalence, Comorbidities, and Risk Factors of Erectile Dysfunction: Results from a Prospective Real-World Study in the United Kingdom. (20th March 2022) - Li, Jim Z.; Maguire, Terence A.; Zou, Kelly H.; Lee, Lauren J.; Donde, Shaantanu S.; Taylor, David G.
Abstract : Objectives . Assessment of erectile dysfunction (ED) burden could improve health outcomes associated with underlying cardiometabolic and psychological causes of ED. This study provided updated real-world evidence (RWE) on ED epidemiology and quantified healthcare resource utilization (HCRU) and health-related quality of life (HRQoL) burden among men with ED in the UK. Methods . This cross-sectional, prospective real-world evidence study was conducted via a self-reported Internet survey in 2018 in the UK general population. Prevalence of ED was estimated; HCRU and HRQoL were compared between men with ED versus without ED via bivariate analysis. Results . Of 12, 490 men included, 41.5% reported ED; 7.5% of men reported severe ED; ED was most prevalent in Wales (44.3%). Men with ED were older (54.1 ± 14.5 vs. 46.8 ± 14.1 years) and often reported modifiable lifestyle risk factors, including smoking (32.8% vs. 26.3%), drinking alcohol (76.1% vs. 71.0%), not exercising (21.7% vs. 19.4%), and being overweight or obese (64.9% vs. 54.6%). Additionally, men with ED more often reported ≥1 comorbid chronic conditions (73.7% vs. 47.7%), including hypertension (31.8% vs. 16.3%), hyperlipidemia (27.6% vs. 14.0%), depression (24.3% vs. 14.6%), anxiety (23.3% vs. 16.6%), and diabetes (15.9% vs. 6.1%) versus men without ED (all, p < 0.001). Nearly half of men with ED (45.3%) were not undergoing treatment for cardiometabolic or psychological comorbidities. Furthermore, men with ED more often reported ≥1 visit to physicians/nurse practitioners and pharmacists in the past year and had significantly lower SEAR total and domain scores than men without ED (all, p < 0.001). Conclusion . ED was highly prevalent in the UK affecting over a quarter of younger men. Cardiometabolic and psychological conditions were common among men with ED and often remained untreated. Higher proportions of modifiable lifestyle risk factors observed among men with ED present an opportunity for healthcare providers to help mitigate the risk of cardiometabolic diseases and incidence of ED.